Asking about Freedom in Polish School. Reflections in the Context of Martin?s Heidegger?s Thought - Archacka, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2017)
In the article I am posing a question on the possibility of the occurrence of freedom in the school educational space, in the light of M. Heidegger?s philosophical concept. The departure point of the undertaken considerations is a thought formed in the essay of ?The question of technology?, where the philosopher presents a technical character of the contemporary civilisation. The aim of the article is to outline the possibility of transition from the presentation concept of education to the thinking about learning understood as discovering the essence of humanity. My analysis of daily school practices will allow me to show those elements, which build a technical essence of school education.